2019
DOI: 10.1101/643296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retroposon Insertions within a Multispecies Coalescent Framework Suggest that Ratite Phylogeny is not in the ‘Anomaly Zone’

Abstract: coalescence methods were developed to address the negative impacts of incomplete lineage sorting on species tree estimation with concatenation. Coalescence methods are statistically consistent if certain requirements are met including no intralocus recombination, neutral evolution, and no gene tree reconstruction error. However, the assumption of no intralocus recombination may not hold for many DNA sequence data sets, and neutral evolution is not the rule for genetic markers that are commonly employed in phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 89 publications
0
13
0
Order By: Relevance
“…Herein, we combine estimates of CBL obtained using genome-scale indel data with information from timetrees and reconstructions of ancestral generation times to yield what we believe to be the first empirical estimates of the relative effective population size (Ne of ancestral lineages in very deep time. Our approach bears some similarity to recently described approaches [81,82] and those of Tiley et al [83], who estimated CBL using binary data (TE insertions and "perfect" transversions, respectively). However, we implemented these analyses in a modified version of the commonly used multispecies coalescent program Accurate Species TRee Algorithm (ASTRAL) [84,85].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Herein, we combine estimates of CBL obtained using genome-scale indel data with information from timetrees and reconstructions of ancestral generation times to yield what we believe to be the first empirical estimates of the relative effective population size (Ne of ancestral lineages in very deep time. Our approach bears some similarity to recently described approaches [81,82] and those of Tiley et al [83], who estimated CBL using binary data (TE insertions and "perfect" transversions, respectively). However, we implemented these analyses in a modified version of the commonly used multispecies coalescent program Accurate Species TRee Algorithm (ASTRAL) [84,85].…”
Section: Introductionmentioning
confidence: 65%
“…Perhaps as importantly as questions of alignment and genome assembly, indels lag far behind nucleotides in terms of 'substitution' models that faithfully describe differences in rates of insertion versus deletion, as well as differences in rate, frequency, and homoplasy associated with differences in indel length and mechanism of gain or loss. We are only beginning to learn their behavior in multispecies coalescent analysis [82,89].…”
Section: Homoplasy and Sequence Alignmentmentioning
confidence: 99%
“…However, the congruence between estimates of the species tree generated using ASTRAL on gene trees and those generated using perfect transversions indicates that intralocus recombination cannot be distorting our topology because the transversion data treats each perfect transversion site as a partially resolved gene tree. Scoring biallelic markers as partially resolved is expected to yield accurate estimates of coalescent branch lengths as long as the markers are truly homoplasy-free (Springer and Gatesy 2019). However, our observation that perfect transversion branch lengths are shorter than those estimated using gene trees (Table 2) suggests that the transversion data are unlikely to be homoplasy-free.…”
Section: Data Type Effects Are Evident In the Gallus Radiationmentioning
confidence: 79%
“…2). First, we employed the protocol outlined previously by Springer and Gatesy (2019). Each retroposon matrix of presence/absence characters was converted into a set of incompletely resolved 'gene trees' with each gene tree representing a single retroposon character and supporting just a single bipartition.…”
Section: Species Tree Estimation Using Retroposon Insertionsmentioning
confidence: 99%
“…Retroposon insertions have commonly been analyzed using one or more variants of parsimony (e.g., Camin-Sokal parsimony [Nikaido et al 1999]; polymorphism parsimony [Suh et al 2015]; Dollo parsimony [Lammers et al 2019]), distance methods (e.g., neighbor joining [Lammers et al 2019]), or networks (e.g., Doronina et al, 2017a;Lammers et al 2019). More recently, Springer and Gatesy (2019) suggested that retroposons have several properties that are well matched to the assumptions of summary coalescent methods such as ASTRAL (Mirarab and Warnow 2015). First, summary coalescent methods assume that ILS is the only source of gene tree heterogeneity.…”
Section: Introductionmentioning
confidence: 99%